Exploring diversion programmes for youth in conflict with the law: a case study of the youth empowerment scheme programme at NICRO, Durban, South Africa - Ntuli, Precious Nolwazi (Acta criminologica, 2019)
Diversion is one of the mechanisms of channelling the youth in conflict with the law away from the criminal justice system through reintegration programmes. Diversion is critical to the achievement of a child justice regime that is compliant with constitutional and international obligations. Despite some success in reducing crime among youth in conflict with the law by means of rehabilitating them through diversion programmes, an illumination of the perspectives and experiences of youth is limited in the literature. This article explores the impact of diversion programmes on a sample of ten youth offenders who had been referred to the Youth Empowerment Scheme Programme of the National Institute for Crime Prevention and Reintegration of Offenders (NICRO) in Durban. The article is based on a study that utilised a qualitative research methodology design and employed purposeful non-probability sampling involving youth who had participated on a diversion programme. The findings of this study demonstrated that youth pleaded guilty not because they were guilty, but in order to avoid being incarcerated. This finding implies that some youth plead guilty to a crime they had not committed due to the arrangements associated with pleading guilty, such as being diverted. It is then recommended that there is a need for further research to evaluate the preliminary inquiry process of diversion programmes in order to assess whether they are conducted in a manner that is just and non-discriminatory. It is further recommended that the Department of Justice should develop mechanisms that will ensure that the rights of these youth are protected during the preliminary inquiry of diversion programmes. Further research is needed to empirically assess how decisions are made during the process of diverting the youth and to establish factors that influence decision of the relevant officials.